Respuesta :

Hey, there!!

Given that:

y = 3x.........(i)

[tex]y = {x}^{2} + 3x - 16.......(ii)[/tex]

Putting the value of y in equation (ii)

[tex] {3x}^{} = {x}^{2} + 3x - 16[/tex]

[tex] {x }^{2} - 16[/tex]=0

[tex]( {x)}^{2} - {4}^{2} = 0[/tex]

[tex](x + 4)(x - 4) = 0[/tex]

Therefore,

Either Or

(x+4)=0 (x-4)=0

x= -4 x= 4

so, x= (+ -)4

And if you wanna get value of y, just keep value of x in equation (i).

y= 3x

y= (3×4) or (3×-4)

y= 12 or -12

{As it is the quadratic equation it has two values. }

Hope it helps....

ACCESS MORE